Structure–odour relationships reviewed in the postgenomic era. (31st May 2015) - de March, Claire A.; Ryu, SangEun; Sicard, Gilles; Moon, Cheil; Golebiowski, Jérôme
Abstract This review reports on the knowledge about odourant–olfactory receptor interactions and their projection within the field of structure–odour relationships (SOR). We provide a list of agonists and odour spaces associated with deorphanized human olfactory receptors. The link between olfactory receptor responses, differential perception and subtleties within odour families is discussed. Copyright © 2015 John Wiley & Sons, Ltd.